Response surface modeling and optimizing conditions for anthocyanins extraction from Hibiscussabdariffa L. (Roselle) grown in Lam Dong, Vietnam - Pham, Tri Nhut; Nguyen, Thuong Nhan Phu; Duc, Lam Tri; Nguyen, Minh Tien; Toan, Tran Quoc; Nhan, Le Thi Hong; Vo, Dai-Viet N.; Vo, Thanh Sang; Bui, Le Minh (IOP Publishing, 2019)
Hibiscus sabdariffa L. (Hs, roselle; Malvaceae) is a common ingredient used in the food and pharmaceutical industries for color and health benefits. Anthocyanins along with protocatechuic acid and quercetin have been recognized as bioactive compounds in Hibiscussabdariffa L. aqueous extracts. In this work, Response Surface Methodology was implemented together with Box-Behnken experimental design to investigate the impacts of process variables on anthocyanin extraction yields from Hibiscus sabdariffa L. (Roselle) grown in Lam Dong, Vietnam. The effects of three independent variables; namely the extraction temperatures of solvent ethanol (X1); the duration of extraction (X2); solid-liquid ratios (X3) on the total anthocyanins content (Y1) were explored. The optimization model showed that with the solid liquid ratio 7.7:1, extraction time 33.29 min, and temperature 56.9°C, the highest anthocyanin concentration of 186.006 mg/L was obtained. Hibiscussabdariffa L. anthocyanin yield detailed significant correlation with high F values, low P values (<0.0001), and desirable determination coefficient (R2 = 0.9770). The resulting quadratic model could be used to predict yields with given conditions. Actual experimental verification and residual testing revealed that the actual anthocyanin yields could be accurately predicted by the model.